2015
DOI: 10.1088/1748-6041/10/5/051001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neurite outgrowth in 3D hydrogel-based environments

Abstract: The ability of peripheral nervous system (PNS) axons to regenerate and re-innervate their targets after an injury has been widely recognized. However, despite the considerable advances made in microsurgical techniques, complete functional recovery is rarely achieved, especially for severe peripheral nerve injuries (PNIs). Therefore, alternative therapies that can successfully repair peripheral nerves are still essential. In recent years the use of biodegradable hydrogels enriched with growth-supporting and gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…To date, several groups have demonstrated that transplantation of MSCs into spinal cord favors nerve regeneration 59 . Moreover, recent studies suggest that MSCs secretome promotes neurite outgrowth 10, 13, 29 . However, it remained unknown the effects of mesenchymal stem cells secretome in CNS neurons, specifically in the axons.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several groups have demonstrated that transplantation of MSCs into spinal cord favors nerve regeneration 59 . Moreover, recent studies suggest that MSCs secretome promotes neurite outgrowth 10, 13, 29 . However, it remained unknown the effects of mesenchymal stem cells secretome in CNS neurons, specifically in the axons.…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal root ganglion explants were used for axonal growth experiments. For that, DRGs from 5 days-old neonatal Wistar-Han rat pups were dissected as previously described [33]. Briefly, DRGs from cervical and thoracic regions of the spine of neonatal rat pups (P5) were dissected and the remnants of peripheral nerve processes were cleaned.…”
Section: Isolation and Culture Of Dorsal Root Ganglion (Drg) Explantsmentioning
confidence: 99%
“…Quantitative assessment of the neurite outgrowth in these assays includes parameters, such as the number of neurites, neurite orientation, and neurite length. Recently, neurite outgrowth in 3D hydrogel-based environments has also been established (Assuncao- Silva et al 2015), allowing to culture neuronal progenitors under diff erent conditions and analyze survival, diff erentiation, and neurite outgrowth (Cruz Gaitan et al 2015).…”
Section: Origin Of Neuritesmentioning
confidence: 99%